2016
DOI: 10.3989/gya.0498151
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafiltration-based degumming of crude rice bran oil using a polymer membrane

Abstract: SUMMARY:Membrane technology has been gaining momentum in industrial processes, especially in food technology. It is believed to simplify processes, reduce energy consumption, and eliminate pollutants. The objective was to study the performance of polyvinylidene fluoride (PVDF) and polyethersulfone (PES) polymeric membranes in the degumming of the miscella of crude rice bran oil by using a bench-scale tangential filtration module. In addition, oil miscella filtration techniques using hexane and anhydrous ethyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 24 publications
0
11
0
1
Order By: Relevance
“…Moreover, the flux drop at the end of the filtration was due to the deposition of a gel on the membrane surface 38,41,42 . The deposited layer is formed because of the phospholipids retained on the membrane surface and pores plugging 14,43 . Fig.…”
Section: Permeate Fluxmentioning
confidence: 99%
“…Moreover, the flux drop at the end of the filtration was due to the deposition of a gel on the membrane surface 38,41,42 . The deposited layer is formed because of the phospholipids retained on the membrane surface and pores plugging 14,43 . Fig.…”
Section: Permeate Fluxmentioning
confidence: 99%
“…The technique of mechanical removal of impurities from oil with bleaching earths can be compared to membrane techniques. Research of Sehn, Gonçalves, Ming [46] have shown a high efficiency (95.5%) of phosphorus removal from oil using polymer membranes. The use of phospholipidase C (PLC) is also effective, resulting in a crude oil with phosphorus content 7.34 ± 0.39 mg/kg [47].…”
Section: Bleaching Earthmentioning
confidence: 99%
“…Degumming of crude vegetable oils using ultrafiltration has been reported in several studies, with authors testing both polymeric (Arora, Manjula, Krishna, & Subramanian, 2006;de Moura, Gonçalves, Petrus, & Viotto, 2005;García et al, 2006;Cecilia Pagliero, Mattea, Ochoa, & Marchese, 2007;Sehn, Gonçalves, & Ming, 2016) and ceramic (Basso, Gonçalves, Grimaldi, & Viotto, 2009;de Souza et al, 2008;Wibisono et al, 2014) membranes for this application. Lin et al (Lin et al, 1997) studied the degumming of 25% cottonseed oil/hexane miscella using two different polymeric membranes with MWCO of 1000 and 15000 Da that achieved phospholipid rejection of 99.4% and 94.6%, respectively.…”
Section: Introductionmentioning
confidence: 98%